Technical results from a trial of the FREO(2) Low-Pressure Oxygen Storage system, Mbarara Regional Referral Hospital, Uganda - Peake, David (PLoS One, 2021)
Increased access to reliable medical oxygen would reduce the global burden of pneumonia. Oxygen concentrators have been shown to be an effective solution, however they have significant drawbacks when used in low-resource environments where pneumonia burden is the heaviest. Low quality grid power can damage oxygen concentrators and blackouts can prevent at-risk patients from receiving continual oxygen therapy. Gaps in prescribed oxygen flow can result in acquired brain injuries, extended hypoxemia and death. The FREO(2) Low-Pressure Oxygen Storage (LPOS) system consists of a suite of improvements to a standard oxygen concentrator which address these limitations. This study reports the technical results of a field trial of the system in Mbarara, Uganda. During this trial, oxygen supplied from the LPOS system was distributed to four beds in the paediatric ward of Mbarara Regional Referral Hospital. Over a three-month period, medical-grade oxygen was made available to patients 100% of the time. This period was sufficient to quantify the ability of the LPOS system to deal with blackouts, maintenance, and an unscheduled repair to the LPOS store.